2021
DOI: 10.1371/journal.pone.0261387
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of combination of organic and inorganic fertilizer on soil properties and microorganisms in a Quaternary Red Clay

Abstract: Quaternary Red Clay (QRC) is the most common planting soil with low soil fertility and low crop yields in Southeast China, with low soil fertility and low crop yields. Many factors can impact the fertility and utilization efficiency of QRC. Here, we conducted a long-term fertilization experiment from 1984 to 2013. Five fertilization measures were carried out, including non-fertilization group; chemical Fertilizer group; 70% chemical and 30% organic fertilizer group; 50% chemical and 50% organic fertilizer grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The quality of soil needs to be sustained when the quality and quantity of food production are enhanced in modern agriculture. To maintain sustainable agriculture, it is essential to reduce the usage of inorganic fertilizers and balance the ecosystem in soil by application of new fertilizers (Young and Ritz, 2000 ; Orr et al, 2011 ; Liu et al, 2021 ). Organic fertilizers and biofertilizers are indispensable for sustainable agriculture (Hernández-Fernández et al, 2021 ; Wang et al, 2021 ; Kumar et al, 2022a ).…”
Section: Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of soil needs to be sustained when the quality and quantity of food production are enhanced in modern agriculture. To maintain sustainable agriculture, it is essential to reduce the usage of inorganic fertilizers and balance the ecosystem in soil by application of new fertilizers (Young and Ritz, 2000 ; Orr et al, 2011 ; Liu et al, 2021 ). Organic fertilizers and biofertilizers are indispensable for sustainable agriculture (Hernández-Fernández et al, 2021 ; Wang et al, 2021 ; Kumar et al, 2022a ).…”
Section: Perspectivesmentioning
confidence: 99%
“…Fertilizers are usually rich in nutrients such as nitrogen, phosphorus, and potassium and can be prepared through different strategies ( Figure 2 ) (Nazir et al, 2021 ; Ngo et al, 2021 ). Fertilizers can be classified into different types based on their components such as mineral fertilizers and methods in manufacture such as organic, inorganic fertilizers, and biofertilizers (Hirel et al, 2011 ; Liu et al, 2021 ; Urmi et al, 2022 ). The application of fertilizer improves the life of human beings while it also causes environmental problems (Herridge et al, 2008 ; Hirel et al, 2011 ; Zilio et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a substitute for inorganic fertilizers, organic fertilizers had a good ecological protection effect ( 9 ). Liu et al ( 10 ) showed that long-term use of organic fertilizers could increase the content of soil organic matter and significantly increased soil microbial biomass. Organic fertilizers was rich in nutrients and met the requirements of ecological agriculture development.…”
Section: Introductionmentioning
confidence: 99%
“…Organic fertilizers was rich in nutrients and met the requirements of ecological agriculture development. Studies showed that organic fertilizers contained a large amount of carbohydrates, which provided a sufficient carbon source for the growth of soil microorganisms ( 10 ). However, organic fertilizers also had some disadvantages such as heavy metal residues and slow onset of effects.…”
Section: Introductionmentioning
confidence: 99%